2010
DOI: 10.1016/j.jadohealth.2010.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glucose Monitoring and Glycemic Control in Adolescence: Contribution of Diabetes-Specific Responsibility and Family Conflict

Abstract: Purpose To examine age and time trends in responsibility for diabetes management tasks and diabetes-specific family conflict and their relationship to blood glucose monitoring (BGM) frequency and blood glucose control (HbA1c). Methods A sample of 147 adolescents (mean=15.5±.4 years) with type 1 diabetes and their caregivers completed measures of diabetes-specific responsibility and family conflict at baseline and six months. BGM frequency and HbA1c were measured during outpatient clinic appointments. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
149
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(166 citation statements)
references
References 37 publications
11
149
0
6
Order By: Relevance
“…Problematic family functioning is associated with unbalanced levels of cohesion (a score < 15 being designated disengaged and > 85 being enmeshed) and flexibility (a score of <15 being rigid and > 85 being chaotic). Reliability of the FACES IV scales has been doi: 10.7243/2050-0866- [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] found to be acceptable for research and clinical purposes with Cronbach's α values for the scales and subscales being; Cohesion = 0.89, Flexibility = 0.84, Rigid = 0.82, Enmeshed = 0.77, Disengaged = 0.87, and chaotic = 0.86 [16] It has also been shown to discriminate between healthy and problematic family functioning [17].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Problematic family functioning is associated with unbalanced levels of cohesion (a score < 15 being designated disengaged and > 85 being enmeshed) and flexibility (a score of <15 being rigid and > 85 being chaotic). Reliability of the FACES IV scales has been doi: 10.7243/2050-0866- [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] found to be acceptable for research and clinical purposes with Cronbach's α values for the scales and subscales being; Cohesion = 0.89, Flexibility = 0.84, Rigid = 0.82, Enmeshed = 0.77, Disengaged = 0.87, and chaotic = 0.86 [16] It has also been shown to discriminate between healthy and problematic family functioning [17].…”
Section: Methodsmentioning
confidence: 99%
“…This can help parents/carers to consider that "the problem is the problem" rather than "the child is the problem" [32]. It has been suggested that such family approaches may 6 doi: 10.7243/2050-0866- [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] be most effective during early to mid-adolescence, helping the child to effectively progress through this developmental stage, with a more individual approach being adopted in late adolescence [13], but this may be to deprive older adolescents of the opportunity to address wider family concerns. However intervention strategies must work within the existing family system, respecting the parental involvement in the diabetes management tasks, and sometimes shifting the question from "how much involvement?"…”
Section: Practice Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[5,21] Research supports ongoing intervention designed to reduce family conflict in order to improve diabetes-related outcomes. [5,8,[22][23][24] However, resources to address family conflict, including access to social work services, family counseling, and psychological services are sparse in clinical diabetes care. The desires of patients to have these services and the evidence that they are related to superior diabetes outcomes should encourage the field to push for routinely integrating them in the diabetes clinic setting.…”
Section: Discussionmentioning
confidence: 99%